Staged isolation of abdominal cavity in generalized peritonitis - Kutovoi А.; Kosulnikov S.; Zavizion E.; Stepanskyi D. (Medičnì Perspektivi)
In the work we present comparative results of treatment of patients with generalized secondary and tertiary peritonitis depending on the way of surgery completion. Patients in group I (n=27) underwent only skin suturing after the surgery, in group II –laporostoma was formed with VAC in the abdominal cavity. We have evaluated the level of microbe contamination and condition after wound surgery, intensity of adhesion process in the abdominal cavity, multiple organ failure after surgery. The use of laporostoma combined with VAC at different stages of generalized peritonitis treatment helps to achieve illness rigress, less number of planned saniations of abdominal cavity. Even after the first use of VAC, quicker clearance of operation wound and appearance of new granulation tis¬sues occurred. In group II in secondary saniation the frequency of fixing of abdominal cavity is developing 31,9% higher (p<0,05) and in the third saniation the use of VAC therapy resulted in growing number of patients with frozen abdomen.